Analisis Tantangan Kebijakan Hak Kekayaan Intelektual terhadap Perkembangan Ekonomi Kreatif dalam Revolusi Industri (UU Nomor 28 Tahun 2014) - Sari, Ameliya Ratna; Khairani, Nisya Hamidah; Dienullah, M. Dhava; Antoni, Herli; Putri, Nasya Aliyyah (Faculty of Law, University of Dr. Soetomo, 2023)
Now, the world is undergoing a transformation known as the industrial revolution and resulting in a creative economy, which affects technological progress based on the principle of human creativity. In this case, intellectual property rights have an important role to provide protection to their citizens for the results they obtain and avoid intellectual property rights infringement. However, in practice, several problems arise with legal policies on intellectual property rights in the Indonesian state. In Indonesia, the protection of intellectual property rights can realize a sense of security, legal certainty and psychological effects, increasing the creator's spirit to continue to innovate.